Global Green Diplomacy Cross-Border Collaboration in Mangrove Conservation as a Blue Carbon Solution - Putu Ayu Sita LAKSMI; I Ketut Johny Pramananda PUTRA; A.A Made Indra Wijaya KUSUMA; Mohd Azlan Bin Abu BAKAR; Gusti Ngurah Danan AGASTIRA (PT Keberlanjutan Strategis Indonesia, 2025)
The existential challenge of climate change demands urgent solutions, with mangrove conservation emerging as a potent nature-based strategy through the Blue Carbon paradigm. This article explores the transformative concept of